The curious history of the heart a cultural and scientific journey - Figueredo, Vincent M. (Columbia University Press, 2023)
This book traces the evolution of our understanding of the heart from the dawn of civilization to the present. Vincent M. Figueredo-an accomplished cardiologist and expert on the history of the human heart-explores the role and significance of the heart in art, culture, religion, philosophy, and science across time and place
Keywords: Heart -- Popular works.; Cardiology -- History.; Heart.; Heart; Cardiology -- history; Cœur -- Ouvrages de vulgarisation.; Cardiologie -- Histoire.; Cœur.; MEDICAL / Cardiology; Cardiology; Electronic books.; History; Popular works